A Review of Medium-Voltage Front-End Converters for Grid-connected Battery Energy Storage Systems - Rahouma, Ahmed (2022)
Medium-voltage power conditioning systems (MV-PCS) are used to interface battery energy storagesystems (BESS) to medium-voltage ac distribution systems. MV-PCS usually includes an ac-dc stage, also referred to as the front-end converter (FEC). In this paper, several FEC topologies are categorized according to the type of BESS connection and evaluated. The specific connections are centralized, distributed, and hybrid. The evaluation is performed in terms of power density, FEC efficiency, andconstruction complexity. Finally, this evaluation is used to provide design guidelines and highlight future research aspects.